The Effect of ESG, Profitability, and Company Size on Capital Structure and Its Impact on Company Value - Rafly Amanda; Herlin Tundjung Setijaningsih (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of Environmental, Social, and Governance (ESG), profitability, and company size on capital structure and its impact on company value in the coal mining sector listed on the Indonesia Stock Exchange (IDX) during the period 2018–2024. This study uses a quantitative approach with the path analysis method to determine the direct and indirect effects between variables. Data were obtained from the annual reports and sustainability reports of ten companies selected through purposive sampling techniques. The results of the study indicate that profitability has a negative and significant effect on capital structure, while ESG and company size do not have a significant effect. Furthermore, profitability and company size have a significant effect on company value, while ESG and capital structure do not have a significant effect. The mediation test with the Sobel Test shows that capital structure does not mediate the effect of ESG, profitability, and company size on company value. This finding indicates that profitability is the main factor that directly influences company value, and capital structure is not an effective intermediary channel in the relationship between these variables.